Basic Spanish - Richmond, Dorothy Devney (Practice makes perfect, 2020)
Whether you are learning on your own or taking a beginning class, Practice Makes Perfect: Basic Spanish will support your study and build your confidence in your new language. Each bite-sized lesson of this bestselling guide focuses on just one key grammar concept, supported by essential vocabulary and clear examples of everyday usage. You will then learn to communicate in authentic Spanish: how to meet new people, engage in small talk, express ideas, and more